Keanekaragaman Jenis Burung di Hutan Adat Sub Suku Afsya, Kampung Bariat Distrik Konda Kabupaten Sorong Selatan Provinsi Papua Barat Daya - Purba, Fitri Dewi Handayani Br; Irwanto, Irwanto; Pattinasarany, Cornelis Karel (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2026)
The customary forest of Sub-Tribe Afsya, Bariat Village, South Sorong Regency, Southwest Papua is a lowland tropical rainforest of approximately 2,500 hectares managed under the indigenous